2015
DOI: 10.1590/0102-311x00012115
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal conditions and associated factors among adults and the elderly: findings from the first National Oral Health Survey in Uruguay

Abstract: The aims of this study were to assess the prevalence of periodontal conditions in the Uruguayan adult and elderly population and its association with socioeconomic and behavioral characteristics. Data from adults (35-44, n = 358) and elderly (65-74, n = 411) who participated in the first National Oral Health Survey, Uruguay, 2011, were used. The survey included a household questionnaire addressing socioeconomic characteristics, and tobacco use. Bleeding on probing (BOP), periodontal pockets (CPI) and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 25 publications
(38 reference statements)
3
23
1
7
Order By: Relevance
“…Other studies were consistent with these data and showed that the prevalence of gingival disease in RA patients was significantly associated with age [16, 32, 33]. A study evaluating the prevalence and severity of gingival disease in 40 RA patients showed that the prevalence of gingival disease was higher in men, smokers, and older patients [34, 35]. Interestingly, a recent report suggested that males had a strong inflammatory response to bacterial infection, and male neutrophils responded to lipopolysaccharide in vitro with increased chemokine expression, and increased osteoclast-driven bone-loss compared to females [36].…”
Section: Discussionsupporting
confidence: 62%
“…Other studies were consistent with these data and showed that the prevalence of gingival disease in RA patients was significantly associated with age [16, 32, 33]. A study evaluating the prevalence and severity of gingival disease in 40 RA patients showed that the prevalence of gingival disease was higher in men, smokers, and older patients [34, 35]. Interestingly, a recent report suggested that males had a strong inflammatory response to bacterial infection, and male neutrophils responded to lipopolysaccharide in vitro with increased chemokine expression, and increased osteoclast-driven bone-loss compared to females [36].…”
Section: Discussionsupporting
confidence: 62%
“…Outros estudos de base populacional, mas que utilizaram um exame periodontal completo (seis sítios em todos os dentes) 16,17 reportaram elevada prevalência e extensão de periodontite (acima de 70%), superiores às estimadas pelo levantamento nacional e também pelo presente estudo. Em outros países da América Latina, embora os dados sejam muito heterogêneos, foram descritas prevalências de PIP superiores às encontradas no Brasil 9,18 .…”
Section: Discussionunclassified
“…PD calibration 0.6 -1.0 inter and intraexaminer the capital) (49) . Age: 35 -44, n=358/ 65 -74, n=411 (59) . Households with no member with university studies showed the worst periodontal conditions.…”
Section: National Studies (Table 2)mentioning
confidence: 99%
“…Lorenzo et al 2015 (59) published data from the first national survey on the most common oral pathologies including peridontopathies. People over 35 were evaluated from 2 probabilistic and representative samples from the whole country.…”
Section: Population Samples On Adults and The Elderlymentioning
confidence: 99%